Hadith #789 - Jami' al-Tirmidhi - Aisha bint Abi Bakr; Ayoub bin Waqd al-Kwfy أيوب بن واقد الكوفي; Bashr bin Mua'dh al-Qdy بشر بن معاذ العقدي; Hisham bin 'Urwa هشام بن عروة; Urwa ibn al-Zubayr عروة بن الزبير (Jami' al-Tirmidhi)
The Messenger of Allah said: “Whoever stays with a people, then he is not to fast without their permission.”
Grade: